The Effects of Affecting Factors Minimize the Students’ Foreign Language Apprehension through Psycho-Social Pedagogy - Meenambal, D.S.; S., Meenakshi (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims at analysing the communication skills of rural learners and the following pedagogical perspectives in classroom teaching. It also examines the differences existing in the teaching mode and its educational practices followed by teachers and learners in relation to the requirement of amenities in the teaching space. A set of rural learners from Vellore district has been chosen for this analysis and given the questionnaire based on classroom amenities, management concern on syllabus, and techniques followed by teachers and learners’ proficiency level. This survey method is carried out based on the self-report questionnaire and identified the obstacles. Taken survey (questionnaire) from 65 students on how their teachers teach to learners and learning environment. The data were analysed by applying the frequency table. Its impact affirms the inadequacy of communication training between learners and teachers’ interaction and between the learners in an authentic situation. From the questionnaire report, the following constraints are followed in the classroom: The interactive learning platform was not given among the learners, which causes dissatisfaction; involvement and commitment from the teachers are not up to the benchmark level, and the absence of following up strategies like activities and techniques seems very less for the rural learners. Discussion and suggestions of this work reflect the same, wherein all educational authorities and teachers have to provide adequate prospects to the rural learners to get rid of their nervousness, reluctance, and communication apprehension. The English language has established its roots firmly in the field of the employment sector, ascertaining it as a language meant for formal communication. This created an urge to achieve mastery in language fluency and accuracy to have proper communication in and around the globe. Subsequently, enhancing oral communication and proficiency are the trending subsistence for learners.